Ukuran Perusahaan, Komite Audit, Opini Audit, Ukuran KAP dan Audit Delay di Perusahaan Transportasi - Putri, Arie Pratania; Utomo, Ricky; Yovenia, Yosevin; Novika, Ayu Cindi (E-Jurnal Akuntansi, 2021)
The purpose of the study is to analyze the effect of the Size of Company, Audit Committee, Audit Opinion and the Size of Public Accountant Firm on Audit Delay in Transportation Companies in Indonesia. Quantitative methods are used in the analysis of this study.The use of purposive sampling technique leaves 28 companies from 46 populations companies, so that the total of samples in this analysis are 84 data. As the dependent variable (Audit Delay) is dummy variable, logistic regression is used in the research process. The result of this study is that partially the independent variable that has an effect is the Audit Opinion while the Size of Company, the audit committee, and the Size of Public Accountant Firm have no effect. Simultaneously, all independent variables have an overall effect on the dependent variable with a significance level of 0.000. Keywords: Company Size; Audit Committee; Audit Opinion; KAP size; Delay Audits.